Optimalisasi Pelayanan Publik tentang Pemberdayaan Masyarakat dan Desa di Desa Anggra Distrik Minyambou Kabupaten Pegunungan Arfak Provinsi Papua Barat - Wonggor, Septinus; Wahyudi, Sigit; Rahman, Abdul (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This research aims to determine the role of the village head in increasing community empowerment in the economic sector in Anggra Village, Minyambou District, Arfak Mountains Regency. The data collection method in this research is descriptive qualitative, where this research was carried out by observation, interviews, and documentation. The data used in this research are primary data and secondary data with the research subjects consisting of the Village Head, BPD, and Community Figures. The research results show that the Village Head in carrying out his role is quite good, this can be seen from the results of improving the community's economy and his role in motivating, facilitating, carrying out his duties, and mobilizing residents in every activity to support success in improving the community's economy. These activities took the form of road construction, bridge construction, field schools, greading and counseling, which were carried out in Anggra Village, Minyambou District, Arfak Mountains Regency, West Papua Province